Design and evaluation of an online course to transfer suspected cases of COVID-19 from pharmacies-drugstores in Colombia - Amariles, Pedro; Monsalve, Mauricio; Ledezma-Morales, Mónica; Rivera-Cadavid, Mónica; Salazar-Ospina, Andrea; Ceballos, Mauricio; Granados, Johan; Hincapié-García, Jaime (Ars Pharmaceutica (Internet), 2021)
Introduction: it is needing to design, implement and evaluate the acceptance, relevance, and usability of an online course aimed at promoting the detection and referral of suspected cases of COVID-19 from pharmacies-drugstores. Method: the design of the course was based on a proposed route for the care of users suspected of COVID-19 attending pharmacies, complemented by information obtained through a search in PubMed/Medline and on Websites of leading organizations in the field. The information was structured in an online course, a formulary was developed and applied to assess the coverage, acceptability, and relevance of the course. Results: an online course (How do we act against COVID-19 from the drugstores?) was designed and organized in 7 units and with key concepts to identify and refer suspected cases of COVID-19 from pharmacies-drugstores, available in https://udearroba.udea.edu.co/externos/my/. From April/2020 to April/2021, 863 persons were registered, 382 (44.3%) finished and were sent the formulary for evaluation the course, which was returned by 240 (62.8%). In this group, the satisfaction with the course and education materials was 95.8% and 97.1%, respectively. Also, 97.9% people assert that the course contribute to identify and to refer suspected cases of COVID-19; and 93.3% that, the navigation through the course provides easy access of the contents. Conclusions: a virtual, open, and usable course is designed, implemented, and evaluated, and although the participants state that the course promoting the detection and referral of suspected cases of COVID-19, from pharmacies-drugstores, it is needing to conduct a study to assess this question.